Визначення людських ресурсів підприємств у перспективах повоєнного відтворення економіки України - Чорна, О.А. (Економічний вісник Донбасу, 2025)
Стаття присвячена уточненню сутності людських ресурсів підприємств, визначенню взаємозв’язку між поняттями «людські ресурси» і «людський капітал». Встановлено, що людські ресурси підприємства – це сукупність працівників підприємства та потенційно залучених осіб, що характеризуються кількісними (структура, чисельність) та якісними (професійні знання, навички, досвід, інтелектуальні напрацювання, здоров’я, здібності, соціальні зв’язки, мотивація) характеристиками, які у разі потреби можуть бути використані для досягнення виробничих, управлінських, інноваційних та інших цілей підприємства. Виділено цілі управління людськими ресурсами підприємств. The article is devoted to clarifying the essence of human resources of enterprises. Despite a significant number of deep and meaningful studies on human resources management, the problem of lack of human resources in Ukraine requires intensification of scientific research in this direction, in particular in the prospects of post-war reconstruction of the economy of Ukraine. The relationship between the concepts of «human resources» and «human capital» is determined. Based on the research conducted, it was established that human resources are one of the main forms of resources, encompassing a set of individuals, their quantitative characteristics (number, demographic structure) and qualitative characteristics (knowledge, abilities, skills, health, motivation, i.e. human capital), which, if necessary, can be involved in economic, social or other productive activities. The features of this definition are the understanding that: human resources are a certain potential for participation (the ability to use the human capital of people); human capital is an internal characteristic of a person for participation; real participation is labor activity, economic, social employment, etc. It is substantiated that at the micro level, human resources characterize people working in enterprises, non-commercial organizations or are self-employed. Let us formulate a definition. Human resources of an enterprise are a set of employees of an enterprise and potentially involved persons, characterized by quantitative (structure, number) and qualitative (professional knowledge, skills, experience, intellectual achievements, health, abilities, social ties, motivation) characteristics, which, if necessary, can be used to achieve production, management, innovation and other goals of the enterprise. The goals of human resources management of enterprises are highlighted.